Sanitasi di Desa Pariwisata: Tinjauan Kritis Atas Praktik, Tantangan, dan Inovasi di Indonesia - Prayogo, Wisnu; Handana, Hindra Karamah Putra; Sitorus, Heri Franata; Tinov, Naufal; Luchmanandri, Rahmadini; Ratnaningsih, Wahyu (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
Sanitation is a critical component of tourism sustainability, influencing visitor satisfaction, public health, and destination competitiveness. In Indonesia, a country renowned for its diverse tourist attractions, sanitation management remains a pressing challenge. This review aims to critically analyze existing practices, identify challenges, and explore innovations in sanitation management across Indonesia's tourism destinations. Using a systematic review approach, data from peer-reviewed articles, government reports, and international tourism indices were synthesized to assess the current state of sanitation in Indonesia’s tourism sector. The findings reveal significant disparities in sanitation infrastructure between urban and rural tourist destinations, compounded by insufficient funding, low public awareness, and inconsistent policy implementation. Innovations such as eco-friendly waste management systems and public-private partnerships are emerging but face scalability and adoption barriers. Comparative analysis with neighboring Southeast Asian countries highlights Indonesia’s need for more comprehensive strategies to meet global sanitation standards. This review underscores the vital role of sanitation in enhancing tourist experiences, protecting environmental health, and improving Indonesia's competitiveness in the worldwide tourism market. Policy recommendations include targeted investment in sanitation infrastructure, community-based sanitation programs, and integration of hygiene standards into sustainable tourism strategies. Future research should further explore the intersection of sanitation, health outcomes, and tourism development to inform effective policymaking and destination management.